2003
DOI: 10.1177/1534735403256332
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation as Cause for Scar Cancers of the Lung

Abstract: The molecular and cellular basis of inflammation has become a topic of great interest of late because of the association between mechanisms of inflammation and risk for cancer. Inflammatory-mediated events, such as the production of reactive oxygen species (ROS), the activation of growth factors (for wound repair), and the altering of signaltransduction processes to activate cell-proliferation (to replace necrotic/apoptotic tissue cells), events that also can occur independently of inflammation, are all consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
1
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(75 citation statements)
references
References 79 publications
0
69
1
2
Order By: Relevance
“…It has been also reported that chronic inflammation is responsible for malignant tumors of epithelial origin including gastric, hepatic, colon, lung, pancreatic, esophageal, bladder and gallbladder cancer (Ardies, 2003;Wislez et al, 2003;Margolis et al, 2007). Despite unknown underlying mechanism, it has been suggested that toxic granules in neutrophils lead to inflammation of the neoplastic tissues, activating monocytes (Coussens and Werb, 2002;Nathan, 2006;Fridlender and Albelda, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been also reported that chronic inflammation is responsible for malignant tumors of epithelial origin including gastric, hepatic, colon, lung, pancreatic, esophageal, bladder and gallbladder cancer (Ardies, 2003;Wislez et al, 2003;Margolis et al, 2007). Despite unknown underlying mechanism, it has been suggested that toxic granules in neutrophils lead to inflammation of the neoplastic tissues, activating monocytes (Coussens and Werb, 2002;Nathan, 2006;Fridlender and Albelda, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Increased WBC count due to chronic inflammation is responsible for the development and progression of malignant tumors of epithelial origin including lung, breast, colon, hepatic, thyroid, prostate, gastric, bladder, intestine, and esophageal cancer. (Ardies, 2003;Wislez et al, 2003;Mantovani et al, 2004;Walsh et al, 2005;Margolis et al, 2007;Goswami et al, 2008;). Margolis et al (2007) reported increased neutrophil, monocyte and mean leukocyte count in patients with endometrial cancer compared to healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…This possibility is indirectly supported by observations of the so-called 'scar carcinomas' (Cagle et al, 1985). Ardies postulated that in many cases lung scarring occurred as a result of spontaneous healing after recurrent TB infection, and by triggering cycles of inflammatory and tissue repair processes generated a favorable environment for tumorigenesis (Ardies, 2003). On the other hand, lung cancer may develop autonomously and then provoke reactivation of latent TB by weakening local immunity.…”
Section: Introductionmentioning
confidence: 93%
“…Dans les poumons, l'inflammation chronique peut ĂȘtre provoquĂ©e par des infections virales ou bactĂ©riennes rĂ©pĂ©-tĂ©es, par une exposition prolongĂ©e Ă  des agents toxiques tels que le tabac ou l'amiante, ou ĂȘtre liĂ©e Ă  des maladies respiratoires chroniques. Cette inflammation chronique pulmonaire peut augmenter le risque de carcinogenĂšse [2,3]. Une des molĂ©cules clĂ©s de l'inflammation est le facteur de transcription NF-B, dont la fonction dans le dĂ©veloppement tumoral dans un contexte d'inflammation chronique a Ă©tĂ© dĂ©montrĂ©e [4,5].…”
Section: Lien Entre L'inflammation Et Les Cancers Pulmonairesunclassified